Impact of macroeconomic variables on Islamic and conventional stock market returns: a panel data approach. (1st September 2020) - Marashdeh, Hazem; Ashraf, Sania; Muhammad, Naeem
This study examines the impact of macroeconomic factors on returns in both conventional and Islamic stock market indices. It uses a multifactor model of five macroeconomic factors: the inflation rate, the money supply, industrial production, exchange rates and short-term interest rates. We employed panel data estimation methods of pooled ordinary least squares, fixed-effects estimations and the random-effects approach, in addition to panel co-integration and causality tests. Monthly data for ten countries were utilised for the sample period January 2009 to December 2016. The results show that real effective exchange rates and the money supply influence returns in conventional stock markets, while exchange rates alone influence returns on Islamic stock markets. The results of the co-integration and causality tests confirm the existence of short- and long-run relationships between the above-mentioned macroeconomic variables and returns to both conventional and Islamic stock markets. These results have important implications for investors and policy-makers as they add new insight on the different impacts of macroeconomic variables on returns in both conventional and Islamic stock markets.